2013
DOI: 10.1186/1465-9921-14-44
|View full text |Cite
|
Sign up to set email alerts
|

Current management of patients hospitalized with community-acquired pneumonia across Europe: outcomes from REACH

Abstract: BackgroundData describing real-life management and treatment of community-acquired pneumonia (CAP) in Europe are limited. REACH (http://NCT01293435) was a retrospective, observational study collecting data on the management of EU patients hospitalized with CAP.The purpose of this study was to understand patient and disease characteristics in patients hospitalized with CAP and to review current clinical practices and outcomes.MethodsPatients were aged ≥18 years, hospitalized with CAP between March 2010 and Febr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
3
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 29 publications
2
47
3
3
Order By: Relevance
“…The average length of stay was considerably longer at Peking University People's Hospital (approximately 21 days) than at Guangdong Provincial Hospital of TCM (approximately 12 days). Overall, the length of stay across both sites was higher than that reported in a large European epidemiology study (12.6 days) (28). There was a higher frequency of initial antibiotic modification in Beijing (60%) than in Guangdong (43%), which may reflect differences in disease severity, but both were considerably higher than that reported in a similar observational study of hospitalised CAP patients in Europe (29%) (28).…”
Section: Resistant Isolates (%) N=5contrasting
confidence: 50%
See 2 more Smart Citations
“…The average length of stay was considerably longer at Peking University People's Hospital (approximately 21 days) than at Guangdong Provincial Hospital of TCM (approximately 12 days). Overall, the length of stay across both sites was higher than that reported in a large European epidemiology study (12.6 days) (28). There was a higher frequency of initial antibiotic modification in Beijing (60%) than in Guangdong (43%), which may reflect differences in disease severity, but both were considerably higher than that reported in a similar observational study of hospitalised CAP patients in Europe (29%) (28).…”
Section: Resistant Isolates (%) N=5contrasting
confidence: 50%
“…Overall, the length of stay across both sites was higher than that reported in a large European epidemiology study (12.6 days) (28). There was a higher frequency of initial antibiotic modification in Beijing (60%) than in Guangdong (43%), which may reflect differences in disease severity, but both were considerably higher than that reported in a similar observational study of hospitalised CAP patients in Europe (29%) (28). However, it is important to note that empiric therapy was only modified if patients later received a microbiological diagnosis and/ or the initial treatment was not effective, and in the current study the modifications were mostly de-escalations of antibiotic therapy based on microbiology test results.…”
Section: Resistant Isolates (%) N=5contrasting
confidence: 38%
See 1 more Smart Citation
“…A review of 46 studies conducted from 11 European countries between 1990 and 2007 found that the mortality among inpatients and outpatients with CAP ranged from 4 to 48% [2]. Furthermore, although recent studies of hospitalized patients with CAP from Europe, Thailand, US/Canada, Europe and Latin America identified mortality rates ranging from of 7.2, 9.6, 13.3, 9.1 and 7.3%, respectively [30][31][32], a large multicentre audit of 16 313 hospitalized CAP patients from the UK found a frighteningly high 30-day mortality rate of 18.5% [33]. These differences in mortality between regions and studies remain unexplained; they are likely to be related largely to case mix with mortality increased in the elderly and patients with comorbidities.…”
Section: Mortalitymentioning
confidence: 93%
“…Author(s) agree that this article remain permanently open access under the terms of the Creative Commons Attribution License 4.0 International License required hospitalization (Blasi et al, 2013). In United States of America, the frequency of CAP is around 3 to 5 cases per 1000 individuals with mortality of 5.0 to 15.0% which were hospitalized.…”
Section: Introductionmentioning
confidence: 95%